DISTRIBUIÇÃO POTENCIAL DA PIAVA, Megaleporinus obtusidens (VALENCIENNES, 1847), NA BACIA PARANÁ-PARAGUAI - SOUZA, Beatriz Cristina de Paula,; BAILLY Dayani,; RÉ Reginaldo,; BATISTA-SILVA, Valéria Flávia, (ANAIS DO ENIC, 2023)
-